(untitled) (Bangladesh Journal of Medical Microbiology, 2011)
This cross sectional study was done from January 2009 to June 2010 in Microbiology department of Dhaka Medical Collage. The study was designed to evaluate the advantages and reliability of dot immunoblot (DB) for identification of antibodies to extractable nuclear antigens (anti-ENA) in autoimmune connective tissue disorder (CTD). Sera from systemic lupus erythematosus patients (n = 37), systemic sclerosis patients (n = 13), rheumatoid arthritis patients(n=11), mixed connective tissue disease patients (n=6), polymyositis patients (n=7), and sjogrens syndrome (n=2)were tested for antinuclear antibody (ANA) by Indirect Immunofluorescence (IIF) on HEp-2 cell and analyzed for the presence of antibodies to RNP, Sm, SSA, SSB, Scl-70, and Jo-1 (anti-ENAs) by dot immunoblot and ELISA. Out of 76sera of autoimmune connective tissue diseases 35 (46.05%) samples were found to be positive by DB and 33 (43.4%)were positive by ELISA. The dot blot assay exhibited 100% sensitivity for SSA, SSB, Scl-70 antibodies and for RNP the sensitivity was 90%; specificity was over 98% for these 4 ENA antibodies. Multiple reactivities were also found in a substantial number of patients sera. No serum was positive for anti-Sm and anti-Jo-1.Healthy controls also revealed no positive reactivity for anti-ENA by DB and ELISA. In conclusion, the dot immunoblot is a valid method for the detection of specific autoantibodies in autoimmune connective tissue disorder. Its most notable advantages are simultaneous detection of several autoantibodies in the same serum and its lower cost. DOI: http://dx.doi.org/10.3329/bjmm.v5i1.15815 Bangladesh J Med Microbiol 2011; 05 (01): 12-15